Penanggulangan Kenakalan Siswa oleh Guru Agama - Nuzzulul Ulum (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
This paper aims to describe the handling of student delinquency by religious teachers. Reality has shown that changing times marked by advances in science and technology always result in social change. In facing such situations, students who are teenagers often have sensitive souls, which in the end quite a few teenagers fall into things that are contrary to moral values, religious norms, social norms and norms of life in society which ultimately Teenagers tend to commit inappropriate actions. This research approach is qualitative research that uses a case study type, while data collection requires observation, interview and documentation methods. In analyzing the data, qualitative descriptive analysis was used. The results of this research show that the forms or types of delinquency of MTs students. Miftahul Ulum Wirowongso, Ajung District, Jember Regency, is classified as a minor delinquent who does not violate the law. Things that cause student delinquency are due to the influence of the family environment, school environment, community environment. Meanwhile, the countermeasures carried out by religious teachers are in the form of preventive, repressive, curative and rehabilitative efforts.